Challenging sustainability in school-based intervention in Nicaragua. Issue 4 (24th March 2021) - Pettigrew, Jonathan; Razzante, Robert; Allsup, Joshua; Lu, Yu; Ray, Colter D.
Abstract : Purpose: The current study identifies successes and limitations of sustaining Dale se Real (DsR) as a school-based educational intervention program related to drugs and violence for 7th and 8th grade students in Nicaragua, Central America. As evidence-based interventions are transported and imported across national borders, issues surrounding their adaptation and sustainability become important targets for investigation. Design/methodology/approach: Interviews were conducted with nine key informants (e.g. school directors, implementers) from seven institutions, four of which sustained DsR and three of which did not. This study explores DsR's fit with the institutions' missions and routines, program adaptability, broader community support and sustainability planning. Findings: Findings demonstrate two emerging views of sustainability within the Nicaraguan schools: a deficit approach and an empowerment approach. These two approaches imply different motivational structures for institutions and also led to the practical finding that developers and trainers need to provide structured or formal ways of empowering schools to continue implementing a program after staff no longer routinely contact them. Originality/value: This study contributes a particular case on what facilitates and impedes sustainability of school-based interventions that can inform future intervention research in Latin American countries.